Design And Characterization Of Long Circulating Lyophilized Vesicular Drug Delivery System For Antineoplastic Agents - ARJUN GOJE,; RAJENDRA C. DOIJAD,; SOMPUR C.K, (International Journal of Pharma and Bio Sciences, 2011)
Gemcitabine is an antineoplastic agent commonly used to treat some types of leukemia as well as cancers. In the present study, long circulating liposomal drug delivery system for Gemcitabine was developed, which will increase the efficacy and reduce the toxicity and target the organs (RES). Long circulating liposomal drug delivery system for Gemcitabine was prepared by thin film hydration method using two different carriers and same coating polymer with different concentrations. Four Formulations were prepared by using DPPC and DSPC as a carrier. All the formulations were compared in terms of particle size, polydispersity index, zeta potential, encapsulation efficiency, invitro release, in vivo tissue distribution and stability. Among those, Formulation F2 and F4 show better results. F2 and F4 were subjected to in vivo studies, where formulation F2 showed lower targeting efficiency towards liver spleen and heart, when compared to the formulation F4. Stability studies of F2 revealed that 4oC is the most suitable temperature for storage of long circulating liposomes.